2009
DOI: 10.1080/09540260902782745
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use disorder: Epidemiology and management

Abstract: This paper provides an overview of the epidemiology of cannabis use, cannabis use disorders and its treatment. Cannabis is the most commonly used illicit drug internationally. While use is decreasing in the developed world, it appears to be stable or increasing in developing countries and some indigenous communities. Early initiation and regular adolescent use have been identified as particular risk factors for later problematic cannabis (and other drug) use, impaired mental health, delinquency, lower educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 58 publications
6
129
0
4
Order By: Relevance
“…An earlier age of onset of regular use was associated with worse performance even after controlling for extent of exposure to cannabis. This is particularly concerning given not only the high prevalence of cannabis use among adolescents per se, but with epidemiological evidence for decreasing age of first use (Degenhardt et al 2000;Degenhardt et al 2008;Copeland and Swift 2009 Age of regular cannabis use .40** .43** *p < 0.05, **p < 0.01, ***p < 0.001 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier age of onset of regular use was associated with worse performance even after controlling for extent of exposure to cannabis. This is particularly concerning given not only the high prevalence of cannabis use among adolescents per se, but with epidemiological evidence for decreasing age of first use (Degenhardt et al 2000;Degenhardt et al 2008;Copeland and Swift 2009 Age of regular cannabis use .40** .43** *p < 0.05, **p < 0.01, ***p < 0.001 …”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is the primary period for experimentation and subsequent initiation of regular cannabis use (Copeland and Swift 2009;Jacobus et al 2009) and a growing literature reports either cognitive deficits in adolescent cannabis users or greater adverse effects among those commencing cannabis use during early adolescence, particularly prior to the age of 17 (Schwartz et al 1989;Ehrenreich et al 1999;Huestegge et al 2002;Kempel et al 2003;Pope et al 2003;Jacobsen et al 2004;Harvey et al 2007;Jacobsen et al 2007;Medina et al 2007;Jacobus et al 2009). Only two studies have reported impaired word list learning in adolescent or early onset young adult cannabis users (Pope et al 2003;Jacobsen et al 2004;Harvey et al 2007), while in a third study, poor performance was associated with lifetime cannabis use despite a lack of significant difference between users and nonusers (Medina et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some interventions are, however, successful in ameliorating the impacts of withdrawal or reducing the social impacts of cannabis use. Work published subsequently reveals a similar pattern (Danovitch and Gorelick, 2012;Copeland and Swift, 2009;Vandrey and Haney, 2009;Elkashef et al, (2008) Budney, et al, 2007Nordstrom and Levin, 2007).…”
Section: Figure 1 Herementioning
confidence: 69%
“…Recognizing early manifestations of cannabis use disorder (CUD) is crucial for identifying those for whom timely intervention might avert further harm. As yet, relatively little is known about the natural history of cannabis dependence [15].…”
Section: Introductionmentioning
confidence: 99%